The association of Conscientiousness and Neuroticism on BMI and health behaviours: exploring the impact of Healthy Neuroticism - Pedersen, Zandra Overgaard; Sørensen, Kathrine; Ewers, Bettina; Dammeyer, Jesper (Frontiers in Psychology, 2025)
BackgroundExisting research in personality traits provides evidence of associations between Conscientiousness, Neuroticism and Body Mass Index (BMI), with a growing interest in the concept of Healthy Neuroticism. However, the associations are not fully understood, and the mitigating role of health behaviours remains insufficiently investigated.MethodsThis cross-sectional study investigated associations between Neuroticism, Conscientiousness, including high and low scores, Healthy and Unhealthy Neuroticism with BMI, and the mediating effects of physical activity and caring about having a healthy and nutritious diet, in a national sample of 21,619 adults. Personality traits were assessed using the Big Five Inventory-10, and health behaviours via self-reported physical activity and attitudes towards a healthy and nutritious diet. Statistical analyses were conducted using Hayes PROCESS macro for mediation with 5,000 bootstrap samples.ResultsThe results demonstrated that Neuroticism and Unhealthy Neuroticism were positively associated with BMI, whereas Conscientiousness and Healthy Neuroticism showed negative associations. Health behaviours both fully and partially mediated the relationship between personality traits and BMI.ConclusionThese findings provide evidence for Healthy and Unhealthy Neuroticism in relation to BMI and health behaviours. Furthermore, findings demonstrate associations between Neuroticism, Conscientiousness and BMI, with physical activity, and diet awareness acting as mediators. Stratified analysis suggests that the role of educational level in these relationships likely reflects underlying differences in health behaviours.